Maternity leave - Regmi, Krishna,Wang, Le (Global Labor Organization (GLO), 2022)
Supporting working mothers to balance their work and childcare responsibilities is a central objective of maternal and parental leave policies. Nearly all countries offer some forms of maternity and family leave programs for childbearing on a national basis. This chapter reviews various types of leave policies available for working mothers (or parents) across countries and whether and how the policies affect women's labor market outcomes, their own and children's health, and child development. The leave policies can also influence women's fertility choices, as well as household specialization and husbands' labor supply. Recent studies also note the potential impacts on employers and coworkers of mothers who are on leave. One message that this chapter draws from the vast literature - with diverse and, in some instances, contradictory findings - is that policy debates should not center around whether or not governments should offer paid leave; rather they should focus on how to design more efficient or optimal leave programs. This chapter discusses some preliminary lessons for designing a leave program.
10419/265367
Keywords: Graue Literatur; maternity leave; parental leave; gender role; birth outcomes; breastfeeding; infant health; children's outcomes; mothers' health; labor supply; fertility; divorce